2013
DOI: 10.14233/ajchem.2013.15038
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents of Taxus baccata L. Leaves from Western and Southern Turkey

Abstract: The genus Taxus L. is classified in the family of Taxaceae and represented by eight species 1,2 . Taxus (yew) species range from North America into Central America and from Eurasia to Southeast Asia 3 . Only one species of Taxus is growing in Turkey, which is Taxus baccata L., a toxic plant and called European yew 4 .Volatile compounds were extracted from T. baccata L. leaves collected from northern Turkey (Black sea region) have been studied by Erdemoglu et al. 5 . However, the geographical place of growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…β ‐Vetivone ( 47 ) and hexahydrofarnesyl acetone ( 48 ), characterizing the leaf EO analyzed in the present study, were identified in the highest relative percentages. The first one is used as a flavor and a fragrance, and has a fresh jasmine odor …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…β ‐Vetivone ( 47 ) and hexahydrofarnesyl acetone ( 48 ), characterizing the leaf EO analyzed in the present study, were identified in the highest relative percentages. The first one is used as a flavor and a fragrance, and has a fresh jasmine odor …”
Section: Resultsmentioning
confidence: 99%
“…The first one is used as a flavor and a fragrance, and has a fresh jasmine odor. [84] A total of nine aldehydes were identified in the headspaces of the analyzed mandrake organs. Hexanal (34), 2-ethyl-2-hexenal (37), nonanal (38) and 2-butyl-2-octenal (42) were present in the highest amounts.…”
Section: Headspace Leaf Volatilesmentioning
confidence: 99%
“…T. baccata chemical composition is very different from the composition of the same species studied elsewhere. The populations of Turkey present as major components 1octene-3-ol, caryophyllene oxide, and hexahydro farnesyl acetone (Yasar 2013) In Serbia, the essential oil of T. baccata is rich in 1octene-3-ol, (3Z) -hex-3-en-1-ol and myrtenol (Stefanovic et al 2016). Another study carried out in Serbia by Radulovic et al (2011) showed that the essential oil of T. baccata exhibits high concentrations of hexahydrofarnesyl acetone, myrenol, (Z) -3-hexenol, senecioic acid and tricosane.…”
Section: Discussionmentioning
confidence: 99%
“…Radulovic et al (2011) in a study on aerial parts of T. baccata, showed that the essential oil is rich in hexahydrofarnesyl acetone, myrtenol, (Z)-3hexenol, 3-methyl-2-butenoic acid and tricosan. The oils from the fresh leaves of T. baccata collected from the Aegean and Mediterranean region of Turkey are dominated by 1-octen-3-ol, (E)-2-hexen-1-ol, caryophyllene oxide, hexahydrofarnesyl acetone and 1-hexanol (Yasar 2013). The essential oils of T. wallichiana leaves contain 3-hexen-1-ol, 2-hexenal, 1-octen-3-ol, 3-octanone and hexadecanoic acid as the main products (Jian-chun et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One of the means to protect this species is to use the re-growing parts of the plant and also finding and applying the component extraction method is of vital importance [10]. Plant species, habitat environment, and height and the method used to extract the components are effective factors in determining the type and amount of components [11,12]. This study aimed to extract the leaf and male cones components of yew and identify its constituents to provide a better perspective about the T. baccata growing in Iran.…”
Section: Introductionmentioning
confidence: 99%